Synthetic Medicinal Chemistry in Chagas' Disease: Compounds at The Final Stage of "Hit-To-Lead" Phase - Hugo Cerecetto; Mercedes González (MDPI AG, 2010)
Chagas' disease, or American trypanosomosiasis, has been the most relevant illness produced by protozoa in Latin America. Synthetic medicinal chemistry efforts have provided an extensive number of chemodiverse hits at the "active-to-hit" stage. However, only a more limited number of these have been studied in vivo in models of Chagas' disease. Herein, we survey some of the cantidates able to surpass the "hit-to-lead" stage discussing their limitations or merit to enter in clinical trials in the short term.